CONTEMPORARY CHALLENGES IN THE BANKING RISK MANAGEMENT - Milojević, Nenad (Poslovna ekonomija, 2017)
Risk management is one of the crucial parts of today’s business banks management. Global economic crisis in the last decade has strongly influence that risk management is having increased importance in the total banking management. Credit risk is still most dominant risk in the banks worldwide. Similar situation is also in the Republic of Serbia. Liquidity, market, operational and other risks are also having increased importance in today’s banking. Still, typical dominant risk of average commercial bank is credit risk. High level of non-performing loans is one of the especially important credit risk contemporary challenges. Banks, regulatory bodies and other involved institutions are intensively working on the solutions for this topic. Methods for the risk management are experiencing significant changes and progress in the recent years. Inevitablyconnected banking topic with previous is capital managementprogress.In this article current situation in the banking risk management will be analysed. It will be shown in which direction risk management will develop. It will be also analysed actual situation in the banking capital management. Experiences from the Republic of Serbia as well as worldwide banking experiences will be taken into consider. The article will outline recommendations for further risk management progress.